2000
DOI: 10.1021/jp001704y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Self-Reactions of Peroxy Radicals Arising from Chlorine-Initiated Oxidation of Chloroethenes

Abstract: The kinetics of the self-reactions of CHCl2CHClO2, CHCl2CCl2O2, and CCl3CCl2O2 have been investigated using a conventional flash photolysis/UV absorption setup at room temperature and at atmospheric pressure. The UV absorption spectra of CHCl2CHClO2, CHCl2CCl2O2, and CCl3CCl2O2 were determined between 230 and 290 nm. All spectra present a broad band centered around 250 nm, with a decrease of cross sections going from the less chlorinated to the more chlorinated radicals. Spectra of CCl3C(O)Cl and CHCl2C(O)Cl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(75 reference statements)
1
8
0
Order By: Relevance
“…The reported data are in very good agreement between 242 and 300 nm, where the data of Villenave et al [821] are smaller by 1-10% than the data of Libuda [445]. At shorter wavelengths the absorption cross-sections reported by Libuda [445] become smaller by up to ~25% at 235 nm than those reported by Villenave et al [821]. The latter authors observed a minimum near 232 nm and increasing cross-sections between 230 and 220 nm.…”
Section: F53supporting
confidence: 56%
See 3 more Smart Citations
“…The reported data are in very good agreement between 242 and 300 nm, where the data of Villenave et al [821] are smaller by 1-10% than the data of Libuda [445]. At shorter wavelengths the absorption cross-sections reported by Libuda [445] become smaller by up to ~25% at 235 nm than those reported by Villenave et al [821]. The latter authors observed a minimum near 232 nm and increasing cross-sections between 230 and 220 nm.…”
Section: F53supporting
confidence: 56%
“…In the wing of the absorption band above 290 nm the data reported by Libuda [445] become smaller by up to about 70% than the data reported by Gillotay et al [282]. Since the data of Villenave et al [821] and Gillotay et al [282] are in good agreement, but Villenave et al [821] measured absorption cross-sections at 10-nm increments only, we list in Table 4-130 the room temperature data of Gillotay et al [282], which are averages over the 500-cm -1 and 5-nm intervals of the high-resolution spectrum (0.015 nm) generally used in stratospheric photodissociation calculations. The temperature studies at 210-295 K by Gillotay et al [282] show an increase of the absorption crosssections with increasing temperature all over the observed wavelength region.…”
Section: F53mentioning
confidence: 87%
See 2 more Smart Citations
“…Earlier, 5 we have studied kinetics of recombination of peroxy radicals (CHCl 2 CHClO 2 , CHCl 2 CCl 2 O 2 , and CCl 3 CCl 2 O 2 ) formed in the chlorine initiated oxidation processes of 1,2 di chloroethene, trichloroethene, and tetrachloroethene, respectively. However, the question about the reac tion products remained open.…”
mentioning
confidence: 99%